ANALISIS FAKTOR PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG PADA AKSEPTOR KB AKTIF DI PUSKESMAS REJOSO - Sukmo, Previ Kuncoro; Sunardi; Haryuni, Sri; Mirasa, Yudied Agung (Journal of Health Science and Prevention, 2024)
The population will become a problem if Indonesia's population increases while the quality of life decreases. Family planning programs are needed to stop uncontrolled growth because a baby boom will occur. Long-term contraceptive methods (MKJP) are very effective and can stop population growth. The purpose of this study was to investigate the various factors that may influence an active family planning acceptor's decision to use MKJP. This study was designed as a cross-sectional study using a simple random sampling method, resulting in 285 acceptors. The analysis used was univariate, bivariate analysis using chi-square test α = 0.05 and 95% CI and multivariate logistic regression. Age was the variable that significantly influenced the choice of long-term contraception, according to multivariate results (p = 0.01; OR = 2.24; CI: 1.17-4.29).